(3JNWjW heQGbHI GdEfJGL (B:s (3efgL cej eY MGdI OQGSjI (B/s - (3GdaVd, eDjO YHO GdMSjfs ((3GdQjGV(B: s (3OQG GdeQjN ddfTQ hGdJhRjY(B, s, 2007)
(3eaGgje YGeI aj JNWjW GdEfJGL, CSGdjH hebheGJ JNWjW GdEfJGL, JNWjW GdEfJGL HGSJNOGe GdSdGSd GdRefjI, GSGdjH eMGSHjI aj JNWjW GdEfJGL, JNWjW GdEfJGL Ydi CSGS GdeONdGJ, GdeaGVdI Hjf GdefJLGJ dENJjGQ GdNdjW GdCbd HGSJNOGe GdHQeLI, GdNWjI hOYe GdbQGQGJ GdEfJGL HGSJNOGe CSGdjH fXQjI GdbQGQ, JNWjW heQGbHI LhOI GdEfJGLs
(3HHdjhZQGajG(B: (3U(B.489 (3edGMb U(B.497s
Keywords: (3EOGQI GdEfJGLs; (3GdJNWjWs; (3eQGbHI GdEfJGLs